"In vitro" pollen germination of Hevea camargoana - Gonçalves, Paulo de Souza; Paiva, João Rodrigues de; Rebello, Antonio P. (Pesquisa Agropecuaria Brasileira, 2014)
A study of pollen viability was carried out aiming to obtain the best medium concentration for pollen germination. Different concentrations of sucrose, glucose, galactose, lactose and mannitol in distilled water with and without boric acid were tested as media for germination of pollen of Hevea camargoana in the laboratory. Twenty percent sucrose with 0.01% boric acid at 25 to 30°C gave the best results. Tube lengths of 74.78 μm were obtained. Pollen tubes emerged within 30 minutes and completed full growth within six hours. Adding 0.01% boric acid increased the percentage germination markedly in all media except in mannitol.